Lamellar ichthyosis. A recurring family case - Sosa Flores, Jorge Luis (2023)
Introduction: Hereditary ichthyosis can be syndromic and non-syndromic, the latter, according to the cutaneous phenotypic expression, include common ichthyosis, X-linked recessive ichthyosis, autosomal recessive congenital ichthyosis, keratinopathic ichthyosis and other forms. Autosomal recessive congenital ichthyosis includes three main phenotypes: harlequin ichthyosis, lamellar ichthyosis, and congenital ichthyosiform erythroderma. We report a clinical case of recurrent lamellar ichthyosis in a family. Case Report: Preterm newborn, has a 6-year-old sister, diagnosed with lamellar ichthyosis. Mother denies consanguinity with husband, and relatives with this disease. At birth, it is observed covered with collodion membrane throughout the skin, ectropion and eclabio. The initial management was Vaseline gauze, artificial tears, wet gauze in the eyes. Currently baths with shower cream, Shampoo and mineral oil, moisturizing creams and lotions and Acitretin, is clearly improving. Conclusions: With the medical history and family history it is possible to diagnose lamellar ichthyosis. Management is multidisciplinary.